Salt Removal by Combining a Permanent Skip Furrow Irrigation and Salt Removal Sheet - Onishi, Junya; Paluashova, Gaukhar K.; Shirokova, Yulia I.; Fujimaki, Haruyuki (Frontiers in Agronomy, 2021)
Skip furrow irrigation (SFI) can save water by irrigating every alternate furrow. Usually, irrigated furrows are altered at every irrigation event. If irrigated furrows are fixed (permanent SFI, PSFI), more water may be saved, and salts accumulate in the dry side of ridge. Salt removal sheet, a method of collecting salts on the sheet laid on the soil surface utilizing high evaporation demand in drylands, may be an efficient measure if the accumulated salt under PSFI can be removed with it. We evaluated the salinity movement and water-saving under PSFI through a field experiment in Uzbekistan. In addition, salt removal sheet was applied to the shoulder of ridge at drier side under PSFI to evaluate the possibility to remove salt with the practice. Results showed that, in PSFI, salts tend to accumulate on dry side of ridge, the amount of irrigation water was halved without large yield reduction. And PSFI + Sheet was able to catch 6.4 % of salts existed above the depth of 10 cm.